Radio Programme on how Small-scale Farmers can Market their Produce - Mubiru, Wasswa (Technical Centre for Agricultural and Rural Cooperation, 2008)
Marketing is becoming increasingly important for small-scale farmers than ever before. Most of the cooperative unions which used to provide outlets to markets for small-scale farmers are no more. There has also been a growth in urban markets, with farm produce making it to the big towns and cities where they fetch better prices. Farmers would also want to have access to good export markets so that they can have better returns for their produce. But how can small-scale farmers take advantage of these opportunities to market their produce? In this radio programme we are going to look at a number of suggestions for small-scale farmers to assist them, for example in making decisions about what to produce, who to sell it to, how to increase its value, and ideas for solving problems with transport and communication.